MAIN HYDROPHYSICAL PARAMETERS OF THE DRAINED SWAMPS OF THE REPUBLIC OF KARELIA AND MURMANSK OBLAST - Sergey A. Lavrov; Igor L. Kalyuzhny (Water sector of Russia: problems, technologies, management, 2020)
Melioration measures at swamps of the Republic of Karelia and Murmansk Oblast, and their successive agricultural use change water/physical properties of this wetland. Changes in potential of soil water that determines of energy of water-soil relationship accompany the peat density increase. The authors state that potential of soil water depends in functional manner on peat moisture and its density. It is fixed that under increase of wetland usage period peat density rises and, consequently, soil water potential rises as well. We suggested the method and calculating formula approximating potential dependency on moisture content within the whole range of its changes. The article defines dependency of moisture conduction on moisture (within the range from 30% to 80% of volume) that is based on relationship between coefficient of moisture conduction and potential.